Mapping of the self-interaction domains in the simian immunodeficiency virus gag polyprotein - Rauddi, Maria Luisa (2011)
To gain a better understanding of the assembly process in simian immunodeficiency virus (SIV), we first established the conditions under which recombinant SIV Gag lacking the C-terminal p6 domain (SIV GagDp6) assembled in vitro into spherical particles. Based on the full multimerization capacity of SIV GagDp6, and to identify the Gag sequences involved in homotypic interactions, we next developed a pull-down assay in which a panel of histidine-tagged SIV Gag truncation mutants was tested for its ability to associate in vitro with GSTSIVGagDp6. Removal of the nucleocapsid (NC) domain from Gag impaired its ability to interact with GSTSIVGagDp6. However, this Gag mutant consisting of the matrix (MA) and capsid (CA) domains still retained 50% of the wild-type binding activity. Truncation of SIV Gag from its N-terminus yielded markedly different results. The Gag region consisting of the CA and NC was significantly more efficient than wild-type Gag at interacting in vitro with GST-SIVGagDp6. Notably, a small Gag subdomain containing the C-terminal third of the CA and the entire NC not only bound to GST-SIVGagDp6 in vitro at wild-type levels, but also associated in vivo with full-length Gag and was recruited into extracellular particles. Interestingly, when the mature Gag products were analyzed, the MA and NC interacted with GST-SIVGagDp6 with efficiencies representing 20% and 40%, respectively, of the wild-type value, whereas the CA failed to bind to GST-SIVGagDp6, despite being capable of self-associating into multimeric complexes.